Informal network structure and knowledge sharing in organizations: An empirical study of a Korean paint manufacturing company - Woojin Yoon; Jaeyun Jeong; Kyoung Won Park (Administrative Sciences, 2021)
This study investigates the potentially different roles of informal social networks in promoting knowledge sharing. Specifically, it aims to examine the effects of the focal subgroup's between-subgroup network size and strength on knowledge sharing with other subgroups and the moderating effect of within-subgroup network strength on the relationship of between-subgroup network size to knowledge sharing. Two different online surveys were conducted to assess social networks and knowledge sharing at a paint manufacturing company located in Gyeonggi Province, South Korea. The final sample consisted of 536 employees in 58 teams. The team-level regression results showed that the focal subgroup's between-subgroup network strength has a significant effect on knowledge sharing with other subgroups, indicating that strong ties among subgroups are more advantageous to external knowledge sharing than weak ties. The results also demonstrated that the focal subgroup's within-subgroup network strength negatively moderates the effect of its between-subgroup network size on knowledge sharing, indicating that higher levels of between-subgroup network size are positively related to external knowledge sharing when within-subgroup network strength is weak and negatively when within-subgroup network strength is strong. The study's findings suggest that strong ties among subgroups and weak ties among subgroup members are advantageous to external knowledge sharing.
Keywords: 350; informal network; knowledge sharing; network size; network strength; social capital